Палеоконтакты населения позднего бронзового века Северо-Восточного Приазовья (по данным минералогического анализа каменных орудий труда) - Горбов, В. Н.; Смирнова, О. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryV. Gorbov, O. Smirnova. Paleocontacts People Late Bronze Age North–East Azov Region (Materials Mineral Analyzes Stone Tools)The article deals the questions about trade communication north-east Azov region in the late bronze age. The stone tools founded in the settlement Shirokay Balka-II and Bezyamynnoe–II was made mineral analyzes. This analyzes allowed to make the conclusion, that the stone raw material entered from north and north-east Donets mountain range. In postzrubnoe (belozersk) time appear north-west trade direction. In this time stone raw material entered in Dniepr region.